Effort to Improve Parental Awareness of Child-Raising Patterns Through Family Parenting Socialization - Tobiin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Family parenting plays a crucial role in shaping children's development and well-being. Initial observations in Sukajati Village, Haurgeulis District, identified suboptimal parenting practices among parents/guardians of Sukahati Elementary School's UPTD, potentially contributing to juvenile delinquency and low motivation for learning. The objective of this Community Service (PkM) activity was to increase parents' knowledge, skills, and awareness in implementing supportive and communicative parenting. The implementation method used was Interactive Counseling Socialization, which involved delivering material through lectures and a dynamic question-and-answer session. This activity was held on Saturday, July 20, 2024, at Sukahati Elementary School's UPTD. Post-activity qualitative analysis showed a very positive response from participants; all respondents stated an increased understanding and awareness of the importance of good parenting and committed to improving open communication with their children. With an average satisfaction score of 9.67 out of 10, this program was declared highly effective in building a harmonious family foundation and supporting children's character development in Sukajati Village.